2018
DOI: 10.1007/s10238-018-0502-9
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR detects high rate of TP53 R249S mutants in cell-free DNA of middle African patients with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is still a major killing malignancy in sub-Saharan Africa. Lifelong intoxication with aflatoxin B1 is considered as one of the primary causes of this situation. The role of aflatoxin in HCC from a given population is commonly estimated through the prevalence of R249S mutation of TP53, a hallmark for previous exposure to the mycotoxin. However, the role of AFB1 is barely known in large part of Africa. We conducted a survey on circulating cell-free DNA from 149 patients with HCC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…A recent study evaluated the frequency ctDNA mutation of TP53 R249S, well known mutation associated with aflatoxin exposure on 149 African HCC patients and 213 control subjects using ddPCR. 54 About a quarter of the HCC patients had TP53 R249S mutation, while it was seen in only 5 to 6% in control groups of individuals with chronic liver disease or healthy subjects. A similar study was conducted in the United States on 218 HCC patients and 96 Hispanic subjects with advanced fibrosis or cirrhosis.…”
Section: Mutations In Ctdnamentioning
confidence: 97%
“…A recent study evaluated the frequency ctDNA mutation of TP53 R249S, well known mutation associated with aflatoxin exposure on 149 African HCC patients and 213 control subjects using ddPCR. 54 About a quarter of the HCC patients had TP53 R249S mutation, while it was seen in only 5 to 6% in control groups of individuals with chronic liver disease or healthy subjects. A similar study was conducted in the United States on 218 HCC patients and 96 Hispanic subjects with advanced fibrosis or cirrhosis.…”
Section: Mutations In Ctdnamentioning
confidence: 97%
“…The p53R249S allelic fraction is an integrated marker of both past AFB1 exposure and the presence of a tumour carrying this mutation, and indicative of HCC. The sensitivity and specificity of the technique used in this study to detect mutant p53 alleles are comparable with those obtained using another highly sensitive technology, the droplet digital PCR, 35 and highlight their potential in assessing this biomarker in liquid biopsy studies for identifying and confirming HCC status as reviewed in 1 study. 36 Moreover, AFB1 exposure could contribute to the low viral load observed in chronic HBV carriers in The Gambia as in vitro AFB1 exposure has been reported to reduce HBV replication.…”
Section: Discussionmentioning
confidence: 53%
“…In the diagnostic setting, R249S mutation of the TP53 gene is hallmark of aflatoxin B1 exposure, one of the major causes of HCC in certain geographic areas. Using droplet digital PCR the authors identified a higher prevalence of this mutation in plasma cfDNAs of HCC in Cameroonian and Central African patients in comparison with control subjects with and without liver disease (almost 25% of patients with HCC and 3%-9% of non-HCC subjects were R249S carriers), suggesting a potential use of this biomarker as an early risk factor for HCC in individuals exposed to aflatoxin B1 [26] . Targeted deep sequencing was used to investigate several cancer genes involved in HCC.…”
Section: Cancer Gene Mutations In Plasma or Serum Cfdnamentioning
confidence: 99%